Factors influencing the likelihood of dental service checkup: results from a survey in Saudi Arabia - Almutairi, Majed; McKenna, Gerry; Alsumaih, Ibrahim; Alhazzaa, Rasha; O’Neill, Ciaran (Frontiers in Oral Health, 2023)
The funding and delivery of healthcare including dental care in KSA is undergoing a process of reform. To inform this it is important that policymakers are aware of the relationships between service use, specific types of use and the factors that influence this. Currently there is a paucity of research in this area in KSA that examines dental service use for check-ups at a national level and none that examines differences in this use across regions or that examines explicitly the role of income in use.: This study uses the most recent version of the Saudi Health Interview Survey to examine the relationships between use of dental services for a check-up and socio-demographic characteristics of respondents. Particular focus is given to differences between regions in service use and the role of sociodemographics within regions. Methods: Data were taken from SHIS 2013. Descriptive statistics (means and standard errors) were used to characterise the sample. Logistic regression analyses were used to examine the relationship between check-ups service use in the past 12 months and a range of covariates including income and region. The analysis was repeated for sub-samples based on specific regions. No attempt was made to impute missing values.Results: 7603 respondents provided complete data for analysis. 51% of the sample was male, 29% were educated at least to degree level 25% reported that they floss at least once per day, 69 % reported that they brushed their teeth at least once per day and 11% that they had visited the dentist for a check-up in the preceding 12 months. Logistic regression analyses revealed income, region and oral hygiene habits to be among the significant determinants of the likelihood of dental check-up in the preceding 12 months. In logistic regression analyses at the regional level different relationships were evident between check-ups service use and socio-demographic characteristics across regions.Region and income are significant determinants of dental service use for check-ups.Differences exist between regions in relationship between socio-demographic characteristics and the likelihood of check-upsservice use. Policy changes should reflect the potential differences they might have across regions for which the role of socio-demographic varies.